Are you sure?
This action might not be possible to undo. Are you sure you want to continue?
Name:_______________________ Date assigned:______________ Band:________
Calculus  Packer Collegiate Institute
Introduction to Simple Properties of Derivatives
Section 1: The obvious and the nonobvious
1. Use WolframAlpha to find the derivative. Even if you think you know the derivative, use the program.
(a)
7
( ) 2 f x x =
(b)
7
( ) 5 f x x = ÷ (c)
7
( ) 1.11 f x x =
(d)
11
( ) 8 h x x = (e)
11
( ) h x h = ÷ (f)
11
( ) 2.3 h x x = ÷
2. Use WolframAlpha to find the derivative. Even if you think you know the derivative, use the program.
(a)
3 2
( ) j x x x = +
(b)
3 2
3 ( ) 4 j x x x ÷ = (c)
3 2
( ) 12 2 j x x x ÷ = ÷
3. For the following, first make an educated guess the derivative of all four functions below .
Then, after you make your guess, use WolframAlpha to find the derivative of all four functions.
(a)
3 2
( ) k x x x =
Guess:_________________________
WA:__________________________
(b)
( )( )
2 2 4
( ) 2 4 3 k x x x x = + +
Guess:_________________________
WA:__________________________
(c)
6
2
( )
x
k x
x
=
Guess:_________________________
WA:__________________________
(d)
3 2
2
3
( )
2 1
x x
k x
x
+
=
+
Guess:_________________________
WA:__________________________
The important mathematical conclusion:
2
Section 2: WHY?
You have seen from WolframAlpha that we can easily find the derivatives of simple functions like
7
( ) 5 f x x =
and
7
( ) 2 g x x = . You know what we’re aiming for: deep understanding. So you’re going to investigate why this
works.
As usual, we’ll start simple. Let’s investigate
2
( ) a x x = ,
2
( ) 2 b x x = ,
2
1
( )
2
c x x = , and
( )
2
( ) d x x = ÷ . The e
2
( ) a x x =
2
( ) 2 b x x =
2
1
( )
2
c x x =
( )
2
( ) d x x = ÷
What does the coefficient in front of the
( )
2
x part of the equation do? How does it transform the parent
function?
÷9 ÷8 ÷7 ÷6 ÷5 ÷4 ÷3 ÷2 ÷1 1 2 3 4 5 6 7 8 9
÷8
÷7
÷6
÷5
÷4
÷3
÷2
÷1
1
2
3
4
5
6
7
8
x
y
÷9 ÷8 ÷7 ÷6 ÷5 ÷4 ÷3 ÷2 ÷1 1 2 3 4 5 6 7 8 9
÷8
÷7
÷6
÷5
÷4
÷3
÷2
÷1
1
2
3
4
5
6
7
8
x
y
÷9 ÷8 ÷7 ÷6 ÷5 ÷4 ÷3 ÷2 ÷1 1 2 3 4 5 6 7 8 9
÷8
÷7
÷6
÷5
÷4
÷3
÷2
÷1
1
2
3
4
5
6
7
8
x
y
÷9 ÷8 ÷7 ÷6 ÷5 ÷4 ÷3 ÷2 ÷1 1 2 3 4 5 6 7 8 9
÷8
÷7
÷6
÷5
÷4
÷3
÷2
÷1
1
2
3
4
5
6
7
8
x
y
3
Now let’s look at the derivative of these functions at 1 x = :
If you were to draw the tangent lines to
each of these four functions at 1 x = , what
do you notice about the slopes of these
tangent lines?
Does this make sense based on your
graphical understanding of what the
coefficient in front of the
2
( ) x does to the
parent graph?
Now we’re going to look at this algebraically:
2 2
2 2 2
0
0
0
0
2
0
2 )
( ) ( )
'( ) lim
( ) ( )
( )
lim
2
lim
(2 )
lim
lim(2 )
(
2
h
h
h
h
h
x h x
a
x
x
x h x
x
h
xh h
h
h x h
h
x h
h x
x
h
÷
÷
÷
÷
÷
+ + ÷
+ ÷
=
+ ÷
=
= +
=
+
=
=
+
2
0
0
0
0
0
0
2
2 2 2
2 2 2
2
2( ) 2( )
'( ) lim
( ) ( )
2( )
lim
(2 )
lim
4 2
lim
(4 2 )
lim
lim(4 2 )
2 ) 2(
4
4
2 ) (2
h
h
h
h
h
h
x h x
b x
x h x
x
h
x
h
xh h
h
h x h
xh h x
xh h x
h
x h
x
÷
÷
÷
÷
÷
÷
+ + ÷
=
+ + ÷
=
=
=
=
+ ÷
=
+ ÷
+
+
+
=
0
0
0
2 2
2 2 2
2 2 2
2
0
0
0
0.5( ) 0.5( )
'( ) lim
( ) ( )
0.5( )
lim
(0.5 )
lim
0.5
lim
( 0.5 )
li
2 ) 0.5(
m
lim( 0.5 )
0.5 ) (0.5
h
h
h
h
h
h
x h x
c x
x h x
x
h
x
h
xh h
h
h x h
h
x
xh h x
xh h
x
x
h
÷
÷
÷
÷
÷
÷
+ ÷
=
+ + ÷
=
+ + ÷
=
=
=
÷
+
+ =
+
+
=
We learned from WolframAlpha that the second term in the binomial expansion is the most important (all the
other terms disappear). Circle all the terms above that involve the second term in the expansion. (The first
one has been done for you.)
Algebraically, we see that a coefficient in front of the parent function
2
( ) a x x = affects the derivative. How?
÷5 ÷4 ÷3 ÷2 ÷1 1 2 3 4 5
÷1
1
2
3
4
5
6
7
x
y
b(x)=2x^2
a(x)=x^2
c(x)=1/2 x^2
d(x)=x^2
4
Terminology: We conclude from a graphical and algebraic investigation this that [ ( )] [ ( )] cf x c f
d d
dx dx
x = · is true.
This is called the constant multiple rule for derivatives.
Section 3: Okay, now what?
Now let’s see about adding these simple functions together. For example, we know from our initial
investigation that if
3 2
3 ( ) 4 j x x x ÷ = , then
2
'( ) 1 6 2 j x x x = ÷ . Why can we take the derivative of each individual
piece (
3
4x and
2
3x ÷ ) separately?
First, let’s investigate this graphically. I’m going to plot two simple functions separately, and then their sum.
Here are two functions plotted separately. Estimate:
(a)
(
'(0)
' 0) g
f ~
~
(b)
(
'(1)
' 1) g
f ~
~
(c)
(
'(2)
' 2) g
f ~
~
(d)
(
'(3)
' 3) g
f ~
~
Here the sum of the two functions ( ) ( ) ( ) h x f x g x = +
Is plotted. Estimate:
(a) '(0) h ~
(b) '(1) h ~
(c) '(2) h ~
(d) '(3) h ~
Do you see a connection between your answers here
and your answers in the box above?
÷4 ÷3 ÷2 ÷1 1 2 3 4
÷4
÷3
÷2
÷1
1
2
3
4
x
y
f(x)
g(x)
÷4 ÷3 ÷2 ÷1 1 2 3 4
÷4
÷3
÷2
÷1
1
2
3
4
x
y
h(x)
5
Now let’s look at the sum of simple functions algebraically.
Let
4
( ) f x x = ,
2
( ) g x x = , and their sum
4 2
( ) ( ) ( ) h x f x g x x x + = + =
Let’s find the derivative of ( ) h x :
0
0
4 2 4 2
4 4 2 2
4 4 2 2
4
0
4
0
( ) ]
]
Step 1:
]
St
[( ) ] [
'( ) lim
( ) ( )
[( ) ] [( )
lim
( ) ( )
[( ) ] [( )
lim
( ) (
ep 2:
Step 3:
) ( ) ( )
[( ) ]
lim
( ) (
)
h
h
h
h
x h x
h x
x h x
x h x x h x
x h x
x h x
x
x h x
x h x x h x
x h x
x
x h x
h
÷
÷
÷
÷
+ ÷
=
+ ÷
  + ÷ + + ÷

+ ÷
\ .
  + ÷ + ÷
=

+ ÷ + ÷
\ .
+
+ + +
=
+
÷
=
+ ÷
2
0
2
[( )
lim
( ) (
]
Step 4: '( ) ( )
)
'
h
x h x
x h
f x g x
x
÷
+ ÷
+
+
+
=
÷
(a) Explain what’s happening from the starting step to Step 1:
(b) Explain what’s happening from Step 1 to Step 2:
(c) Explain what’s happening from Step 2 to Step 3: Answer: We are using a property of limits that we did
not emphasize: The limit of a sum is the same as the sum of the limits.
(d) Explain what’s happening from Step 3 to Step 4:
Okay, this is a lot of algebra… let’s keep our eyes on the prize. What have we just evidenced?
6
Terminology: We conclude from a graphical and algebraic investigation this that
[ ( ) ( )] [ ( )] [ ( )]
d d d
dx dx dx
f x g x f x g x + = + is true. This is called the sum rule for derivatives. The derivative of a
sum of functions is equal to the derivative of the sums.
Section 4: Conclusion
These two rules (the constant multiple rule for derivatives and the sum rule for derivatives) together are
awesome because they allow us to take the derivative of:
7 4 3
( ) 5 2 2 4 1 Emi io x x x x x l ÷ + + ÷ =
'( ) Emilio x =
And through this investigation, we also have a sense of why the derivative is so easy to deal with.
Bonus challenge:
Take a moment and flip back through this packet. Do you think you can conclude that there is a product rule
for derivatives that looks like: [ ( ) ( )] [ ( )] [ ( )]
d d d
dx dx dx
f x g x f x g x · = · ? What would give you evidence in
support or against this being true?
This action might not be possible to undo. Are you sure you want to continue?
Use one of your book credits to continue reading from where you left off, or restart the preview.